Keiserkult: fremmed kult i det romerske samfunn? - Håland, Evy Johanne (Religionsvidenskabeligt Tidsskrift, 1993)
It has been claimed that, originally, the divinity of the living emperor was alien to traditional Greek and Roman religion. This article tries to show that elements which are introduced with a foreign cult - the cult of the living emperor - may be latent in the traditional cult - the cult of the dead, the ancestor-cult, the need for a present benefactor and subsequently a cult to him - which then become relevant. The socalled foreign cult of the emperor, in this way, filled a gap. Even if this new god was foreign in relation to the traditional gods, i.e. his name, the essence in the cult might on the other hand be something which was aalready present. The way of approaching the problem is from a comparative analysis of ancient Graeco-Roman soiety and present-day society in southern Italy and Greece. The comparison is based on certain religious festivals.